Increasing demand for school counselling through a lay counsellor-delivered classroom sensitisation intervention: a stepped-wedge cluster randomised controlled trial in New Delhi, India. Issue 6 (25th June 2021) - Parikh, Rachana; Hoogendoorn, Adriaan; Michelson, Daniel; Ruwaard, Jeroen; Sharma, Rhea; Bhat, Bhargav; Malik, Kanika; Sahu, Rooplata; Cuijpers, Pim; Patel, Vikram
Abstract : Introduction: We evaluated a classroom-based sensitisation intervention that was designed to reduce demand-side barriers affecting referrals to a school counselling programme. The sensitisation intervention was offered in the context of a host trial evaluating a low-intensity problem-solving treatment for common adolescent mental health problems. Methods: We conducted a stepped-wedge, cluster randomised controlled trial with 70 classes in 6 secondary schools serving low-income communities in New Delhi, India.The classes were randomised to receive a classroom sensitisation session involving a brief video presentation and moderated group discussion, delivered by a lay counsellor over one class period (intervention condition, IC), in two steps of 4 weeks each. The control condition (CC) was whole-school sensitisation (teacher-meetings and whole-school activities such as poster displays). The primary outcome was the proportion of students referred into the host trial. Secondary outcomes were the proportion of students who met mental health caseness criteria and the proportion of self-referred adolescents. Results: Between 20 August 2018 and 9 December 2018, 835 students (23.3% of all students) were referred into the host trial. The referred sample included 591 boys (70.8%), and had a mean age of 15.8 years, SD=0.06; 194 students (31.8% of 610 with complete data) met mental health caseness criteria. The proportion of students referred in each trial conditionwas significantly higher in the IC (IC=21.7%, CC=1.5%, OR=111.36, 95% CI 35.56 to 348.77, p<0.001). The proportion of self-referred participants was also higher in the IC (IC=98.1%, CC=89.1%, Pearson χ 2 (1)=16.92, p<0.001). Although the proportion of referred students meeting caseness criteria was similar in both conditions (IC=32.0% vs CC=28.1%), the proportion weighted for the total student population was substantially higher in the IC (IC=5.2%, CC=0.3%, OR=52.39, 95% CI 12.49 to 219.66, p<0.001). Conclusion: A single, lay counsellor-delivered, classroom sensitisation session increased psychological help-seeking for common mental health problems among secondary school pupils from urban, low-income communities in India. Trial registration number: NCT03633916 .